2010
DOI: 10.1186/1471-2091-11-38
|View full text |Cite
|
Sign up to set email alerts
|

Sex-different hepatic glycogen content and glucose output in rats

Abstract: BackgroundGenes involved in hepatic metabolism have a sex-different expression in rodents. To test whether male and female rat livers differ regarding lipid and carbohydrate metabolism, whole-genome transcript profiles were generated and these were complemented by measurements of hepatic lipid and glycogen content, fatty acid (FA) oxidation rates and hepatic glucose output (HGO). The latter was determined in perfusates from in situ perfusion of male and female rat livers. These perfusates were also analysed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 82 publications
4
27
1
Order By: Relevance
“…On the other hand, these disease-related changes in transcripts and metabolites might only be a consequence of reduced insulin sensitivity and/or hyperglycaemia. However, the sex differences observed in this study are similar to those described in healthy rats, with 50% of the sexdependent genes from this study being similar to those observed in SD rats (Gustavsson et al 2010). These include gene products such as glycerol-3-phosphate acyltransferase and acetyl-coenzyme A synthetase 2 (being female-predominant and reduced upon high-fat feeding) and lactate dehydrogenase A and CPT-1a (being male-predominant and induced upon high-fat feeding).…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…On the other hand, these disease-related changes in transcripts and metabolites might only be a consequence of reduced insulin sensitivity and/or hyperglycaemia. However, the sex differences observed in this study are similar to those described in healthy rats, with 50% of the sexdependent genes from this study being similar to those observed in SD rats (Gustavsson et al 2010). These include gene products such as glycerol-3-phosphate acyltransferase and acetyl-coenzyme A synthetase 2 (being female-predominant and reduced upon high-fat feeding) and lactate dehydrogenase A and CPT-1a (being male-predominant and induced upon high-fat feeding).…”
Section: Resultssupporting
confidence: 70%
“…Furthermore, a significant difference between males and females developing diabetes as a function of dietary fat content is accompanied by a difference in triglyceride/apolipoprotein B ratios (Corsetti et al 2000), with females secreting more triglyceride-enriched lipoprotein particles. This is in line with results obtained in healthy Sprague-Dawley (SD) rats, with females expressing higher levels of lipogenic genes in their livers (Gustavsson et al 2010) as well as having a greater capacity for hepatic uptake of long-chain fatty acids (FAs), synthesis of triglycerides and assembly of very-low-density lipoprotein (VLDL) particles (SolerArgilaga et al 1975, Soler-Argilaga & Heimberg 1976, Kushlan et al 1981.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…In addition, our data also demonstrated that the female rats showed trends to increase blood sugar level following mulberry administration much more than male. Based on the previous data which reported the difference in carbohydrate and fat metabolism between male and female (Gustavsson et al, 2010) and high carbohydrate especially fructose content in mulberry fruits, we did suggest that the increase blood sugar level in female rat might be associated with the lower carbohydrate metabolism in female rat. However, all changes observed in this study were still in normal range.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, sex hormones imprint a sex-dependent pattern of pituitary GH hormone secretion which is a major player in establishing and maintaining the sexual dimorphism of hepatic gene transcription that emerges in rodents at puberty. Sexdependent expression and GH regulation characterizes several families of hepatic genes involved in endo-and xenobiotic metabolism as well as relevant metabolic functions (e.g., lipid metabolism); 20-30% of all hepatic genes has a sex-specific expression pattern in rodents (Tannenbaum et al, 2001;Stahlberg et al, 2004;Gustavsson et al, 2010). Most of these hepatic sex differences are explained by the female-specific secretion of GH, through the induction of female-predominant transcripts and suppression of male-predominant.…”
Section: Gh and Sexual Dimorphism Of Hepatic Physiologymentioning
confidence: 99%